2009
DOI: 10.1123/mcj.13.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Adolescence: A Transient Period of Proprioceptive Neglect in Sensory Integration of Postural Control

Abstract: In the current study, we adopted the hypothesis that the body scheme disturbances occurring during adolescence might lead subjects to transiently neglect proprioceptive information and that adolescents might rely more strongly on vision to control their orientation and stabilize their body. To check this point, we asked adolescents 14-15 years to maintain vertical stance while very slow sinusoidal oscillations in the frontal plane were applied to the supporting platform at 0.01 Hz (below the detection threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
3
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 0 publications
7
59
3
1
Order By: Relevance
“…Adolescence is a dynamic period of physiological and psychological transition. The period between 14 and 15 years is characterized by a degradation of postural orientation and body stabilization because of a transient neglect of proprioceptive cues (Viel et al, 2009). The present results confirmed the existence of a turning point at around 14-15 years when performing a dual task.…”
Section: Age-related Differences In Postural Performancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescence is a dynamic period of physiological and psychological transition. The period between 14 and 15 years is characterized by a degradation of postural orientation and body stabilization because of a transient neglect of proprioceptive cues (Viel et al, 2009). The present results confirmed the existence of a turning point at around 14-15 years when performing a dual task.…”
Section: Age-related Differences In Postural Performancesmentioning
confidence: 99%
“…This adaptive capacity of the central nervous system contributes to a more stable and flexible control of upright stance and already exists in children 4 to 10 years of age (Bair et al, 2007). As adolescents strongly rely on visual cues for body stabilization (Viel et al, 2009), they adapted to the degradation of proprioceptive information similarly to the adults.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…5-9 years is even less well developed, we suggest that this study be replicated with a population that spans the primary school age years. In addition, given that data also suggests that at age 14-15, adolescents enter a period of 'proprioceptive neglect' it would also be important to investigate how standing desks affect manual control in children older than which we have already studied (28).…”
Section: Discussionmentioning
confidence: 99%
“…(20,25) Consequently, balance control is not completely optimal as in adults, but the posture control process in 10 to 12-year-olds presents less variability than in 6 to 8-year-olds. (20,26,27) It was also found that children and teenagers seem to have temporal organization with sensory afferent information for the head, vision, and feet, working together, to control posture, (25) but their CNS maturation is not at the same level. This could explain the difference observed in children and adolescents.…”
Section: Interaction Between Subjects Of Different Agesmentioning
confidence: 99%